PENINGKATAN HASIL BELAJAR SISWA PADA MATERI I PRINSIP-PRINSIP PENYELENGGARAAN ADMINISTRASI MELALUI MODEL KOOPERATIF SNOWBALL THROWING - Iyailisa, ; Sri Inah, (Pendidikan Ekonomi, 2012)
This study is aimed to find out the teacher and student activities to enhance the learning outcomes by applying cooperative learning method type snowball throwing. This study applies the class action research for 3 cycles. The result of the study shows the teacher capability in handling the class is good enough, the students activities also increased, while the learning outcomes both individual and classical comprehensiveness shows increased, The classical comprehensiveness in the pre-test is 11% while in the first cycle post-test is 30, 56, second cycle is 80,56% and the third cycle is 100%.